Patient Perspectives on Nurse Practitioner Care in Oncology in Canada. Issue 5 (12th June 2017) - Stahlke, Sarah; Rawson, Krista; Pituskin, Edith
Abstract: Purpose: The purpose of this study was to add to what is known about patient satisfaction with nurse practitioner (NP) care, from the perspective of breast cancer patients who were followed by an NP. Methods and Design: This study utilized Interpretive Description, a qualitative method aimed at making sense of the experiential aspects of health care and developing practical knowledge for improved care. Nine patients receiving NP‐led care in an outpatient breast cancer clinic were interviewed about their perspectives on and experiences with NP‐led care. Interview transcripts were thematically analyzed. Findings: The NP role has long been regarded as a way of addressing many contemporary health system problems, although there continue to be barriers to the effective utilization of the role, including public and patient misunderstandings. This study revealed that, despite persistent traditional role understandings about health professionals, the patient participants appreciated the benefits of NP care and were highly satisfied with both the physical care and holistic support they received during the course of their treatment. Conclusions and Clinical Relevance: Today's healthcare system is characterized by accessibility issues, unmet patient need, workforce issues, and funding pressures. This research supports and enriches what is known about the benefits and usefulness of NP‐provided care from the viewpoint of those receiving the care. The findings offer guidance to NPs in the clinical setting regarding patient needs and optimal care strategies.